Dampak Pemaksaan Pembelajaran Daring Dalam Pendidikan Islam Selama Pandemi COVID-19 Perspektif Neurosains - Faturrahman 'Arif Rumata; Suyadi Suyadi (Faculty of Sharia and Law UIN Syarif Hidayatullah Jakarta, 2021)
Online learning in the midst of the COVID-19 pandemic was chosen to be a solution in replacing conventional learning which has had a serious impact on students. Limited internet access and the lack of creativity and innovation in the learning concept make students traumatized by education in undergoing the learning process. This paper wants to examine the impact of coercion in online learning during the COVID-19 pandemic as well as the impact on the brains of students. The research data comes from digital literature such as online news, journals, websites, and online documents. The collected data is then reduced and constructed into a new, whole and fresh concept. Data analysis was performed using content analysis that emphasizes intertextuality and meaning creativity. The results showed that the difficulties of online learning due to limited access and poor learning concepts created new problems for students, namely the weakening of student achievement. Students who are unable to access learning and understand learning material properly are not able to achieve competence. This condition will reduce the quality of education. Keywords: Online Learning, the impact of coercion, COVID-19, Islamic Education AbstrakPembelajaran daring di tengah pandemi COVID-19 dipilih menjadi solusi dalam menggantikan pembelajaran konvensional telah menimbulkan dampak serius bagi para peserta didik. Terbatasnya akses internet dan minimnya kreativitas dan inovasi dalam konsep pembelajaran membuat peserta didik menjadi trauma edukasi dalam menjalani proses pembelajaran. Tulisan ini ingin menguji seberapa besar dampak pemaksaan dalam pembelajaran daring selama masa pandemi COVID-19 serta dampak terhadap otak peserta didik. Data penelitian ini bersumber dari literatur digital seperti, berita online, jurnal, website, maupun dokumen-dokumen online. Data-data yang terkumpul, kemudian direduksi dan dikonstruksi menjadi konsep baru yang utuh dan fresh. Analisis data dilakukan dengan menggunakan analisis isi yang mengedepankan intertekstualitas dan meaning creativity. Hasil penelitian menujukkan bahwa kesulitan pembelajaran daring akibat keterbatasan akses dan konsep pembelajaran yang buruk menimbulkan masalah baru bagi para peserta didik yakni melemahnya prestasi belajar siswa. Siswa yang tidak mampu mengakses pembelajaran dan memahami materi pembelajaran dengan baik sama dengan tidak dapat mencapai kompetensi. Kondisi ini akan menurunkan mutu pendidikan. Kata Kunci: Pembelajaran Daring, Dampak Pemaksaan, COVID-19, Pendidikan Islam